The potential of technology in education. (c2016) - Zain, Farah (2016)
Nowadays, considering the great developments of technology in all aspects and its fast widespread among students in Lebanon, we can describe the new generation as smart. The new generation uses the information and communication technology (ICT) to a big extent. As students in Lebanon gain the chance to use the new technology more, especially tablets (including iPads) for education purposes, their passion for attending classes and gaining knowledge might increase. Thus, there is a need to enhance today‟s teaching styles using new learning technologies. Therefore, integrating this kind of information technology (tablets) into the learning process among school students has become an important area to examine and explore. Nevertheless, the importance of this process is subject to debate amongst educators in the schools operating in Lebanon. While some support the idea of integration, opponents claim that tablets‟ costs outweigh their benefits. Questions such as: “Are our schools ready for the technology integration in classrooms?” and “will these technologies contribute to better learning performance?” need to be answered. This study aims at examining the integration of tablets in teaching English in a third grade class at a school operating in Lebanon. A quasi-experimental design was deployed to assess the impact of tablet use on the performance of students and to check whether this technology integration in teaching results in significant differences in the students‟ learning outcomes. A conceptual model was developed based on a theoretical framework combining the Gamification in education Theory (Pelling, 2011) and the Theoretical Extension of the Technology Acceptance Model (Venkatesh & Davis, 2000). Regression analysis was deployed, and results showed that teachers‟ perceived usefulness of tablets in classrooms is determined by the level of perceived school support and their perceived computer self-efficacy. Results also showed that students‟ satisfaction is influenced by the device characteristics as well as their perceived fun and engagement. The quasi-experiment revealed in general that the use of tablets may contribute to better performance among students in gaining the English language skills.